The Gulf Achievement of Cholesterol Targets in Out-Patients Study (GULF ACTION): Design, Rationale, and Preliminary Results - Albackr, Hanan B; Al Waili, Khalid; Almahmeed, Wael; Jarallah, Mohammad A.; Amin, Mohammad I; Alrasadi, Khalid; Batais, Mohammed A.; Almigbal, Turky H.; Youssef, Ali; Alghamdi, Mohammad; Al Shehri, Mohammad; Ahmad, Islam; et al. (Current Vascular Pharmacology, 2023)
Aim: To assess the current dyslipidemia management in the Arabian Gulf region by describing the demographics, study design, and preliminary results of out-patients who achieved low-density lipoprotein cholesterol (LDL-C) goals at the time of the survey. Background: The Arabian Gulf population is at high risk for atherosclerotic cardiovascular disease at younger ages. There is no up-to-date study regarding dyslipidemia management in this region, especially given the recent guideline-recommended LDL-C targets. Objective: Up-to-date comprehensive assessment of the current dyslipidemia management in the Arabian Gulf region, particularly in view of the recent evidence of the additive beneficial effects of ezetimibe and proprotein convertase subtilisin/kexin-9 (PCSK-9) inhibitors on LDL-C levels and cardiovascular outcomes. Methods: The Gulf Achievement of Cholesterol Targets in Out-Patients (GULF ACTION) is an ongoing national observational longitudinal registry of 3000 patients. In this study, adults ≥18 years on lipidlowering drugs for over three months from out-patients of five Gulf countries were enrolled between January 2020 and May 2022 with planned six-month and one-year follow-ups. Results: Of the 1015 patients enrolled, 71% were male, aged 57.9±12 years. In addition, 68% had atherosclerotic cardiovascular disease (ASCVD), 25% of these patients achieved the LDL-C target, and 26% of the cohort were treated using combined lipid-lowering drugs, including statins. Conclusion: The preliminary results of this cohort revealed that only one-fourth of ASCVD patients achieved LDL-C targets. Therefore, GULF ACTION shall improve our understanding of current dyslipidemia management and “guideline gaps” in the Arabian Gulf region.
Keywords: cardiovascular diseases. secondary prevention